C-embedding, Lindelöfness, and Čech-completeness - Dow, Alan; Hart, Pieter; van Mill, Jan; Vermeer, Hans (Topology Proceedings, 2025)
We show that in the class of Lindelöf Čech-complete spaces the property of being C-embedded is quite well-behaved. It admits a useful characterization that can be used to show that products and perfect preimages of C-embedded spaces are again C-embedded. We also show that both properties, Lindelöf and Čech-complete, are needed in the product result.